Quality of life and spatial inequality in London. (January 2014) - Higgins, Paul; Campanera, Josep; Nobajas, Alexandre
In contrast to London's image as a global city and its position as the most affluent region in Europe, the formally established empirical evidence assembled in this paper suggests that spatial inequality in the capital is a key economic and social problem that is unlikely to be resolved by the prevailing localism doctrine of the 'big society'. Isolated from an initial and non-discriminate England-wide clustering analysis of 73 Audit Commission-defined quality of life indicators, the results of our study reveal that pivotal to London's prevailing quality of life distribution is the influence of deprivation, health and educational inequalities, all of which are masked at a pure 'inner' and 'outer' London comparison, capable only of distinguishing the city's borough-level transport and community safety diversity. The policy implications of our study are duly considered and several methodological insights are advanced for future research.